Harvesting vibration energy to piezo-catalytically generate hydrogen through Bi2WO6 layered-perovskite. (December 2020) - Xu, Xiaoli; Xiao, Lingbo; Wu, Zheng; Jia, Yanmin; Ye, Xiang; Wang, Feifei; Yuan, Biao; Yu, Yi; Huang, Haitao; Zou, Guifu
Abstract: Vibration energy sources are nearly ubiquitous in our daily life, for instance, walking, automobile engine, heartbeat, noise, etc., occurring almost whenever and wherever possible. It would be an interesting and exciting breakthrough in the field of energy, if all these energies could be gathered and utilized. Piezoelectric materials make it possible, which can convert vibration energy into electric energy by inducing positive and negative electric charges. Up to now, there has rarely reported on hydrogen generation by piezoelectric materials utilizing vibration energy. Here, an efficient piezo-catalytic hydrogen generation in the layered-perovskite bismuth tungstate (Bi2 WO6 ) nanoplates is carried out through harvesting vibration energy. The yield of hydrogen can achieve 1147.8 μmol g −1 after 6 h vibration with the rate of hydrogen generation of 191.3 μmol g −1  h −1 . The conduction band level of H + /H2 is more positive than the minimum of conduction band of Bi2 WO6 nanoplates, enabling the reduction of water to generate hydrogen. Converting vibration energy into useful clean hydrogen energy can not only make use of waste energy, but also be expected to solve the problem of energy shortage, which is potential in developing the clean hydrogen energy in future. Graphical abstract: Image 1 Highlights: Vibration energy was harvested to piezo-catalytically generate hydrogen. The yield of hydrogen can achieve 1147.8 μmol g −1 after 6 h. The piezo-catalysis provides potential application in hydrogen generation utilizing the natural vibration energy.